Soil-transmitted Helminths Infection among Primary School Students: which Policy bhould be Emphasized? - Bumi Zulheri Herman; Ranisa Handayani Ramlan; Ferawati Rahmat Wahab (International Journal of Public Health Science (IJPHS), 2018)
Soil Transmitted Helminths is a neglected disease and remain untouched in Balikpapan despite of its deteriorating effects on child health. A cross-sectional study to reveal the actual infection among school-age children in Balikpapan was conducted from January-March 2016 involved 101 students from 10 schools. All subjects and parents were interviewed using validated questionnaire followed by stool examination. All data underwent univariate and bivariate test using fisher exact’s test, ANOVA and logistic regression test (95% CI).  Rate of positive infection was 62.4%. Associated risk factors were, routine hand wash (p=0.004 OR=0.050), taking oral prophylaxis (p=0.001 OR=0.182), use of footwear (p=0.009 OR=2.529), involved in “Young Doctor Program” or other health promotion program (p=0.014 OR 0.324) and the type of toilet at home (p=0.048). Knowledge about worm infection (p=0.659), history of previous worm infection (p=0.768) and access to clean water at home (p=0.361) were insignificantly associated with infection rate. Community service (such as “The Clean, Green And Healthy” program) (p=0.037 OR 0.395) and Community Health Care (p=0.000 OR 0.155) were associated with lower risk of infection. Regression test shows that community health care and oral prophylaxis were the most influencing factor and these factors should be considered as the main focus of intervention.